Faktor-faktor yang mempengaruhi fungsi kognitif pada epilepsi - Rika Haryanti; Yazid Dimyati; Johannes H Saing (Fakultas Kedokteran USU, 2017)
Epilepsy is the cause of morbidity in children, which can affect cognitive function. Risk factors such as age of onset, seizure type, seizure frequency, type of epilepsy syndrome, pathological conditions in the brain as well as the negative effects of the use of anti-epileptic drugs are several interacting factors influence the cognitive function so it is important to know how large the influence of these risk factors.Keyword : epilepsy, seizure, cognitive